USM SIGNS MOA WITH GLODON SOFTWARE SDN BHD TO STRENGTHEN INDUSTRIAL NETWORKING - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 6 May 2016 Universiti Sains Malaysia (USM) through the School of Housing, Building and Planning (HBP) signed a Memorandum of Agreement (MoA) with Glodon Software Sdn. Bhd. on 28th April 2016 at Nexus Conexxion, Bangsar South, Kuala Lumpur.